Evaluation of mixture characteristics of warm mix asphalt involving natural and synthetic zeolite additives - Topal, Ali; Sengoz, Burak; Kok, Baha Vural; Yilmaz, Mehmet; Dokandari, Peyman Aghazadeh; Oner, Julide; Kaya, Derya (Elsevier Sci Ltd, 2014)
Concerning global warming and economical issues, many recent studies try to introduce innovative technologies applying lower temperatures with higher performance characteristics as alternative solutions for hot mix asphalt (HMA) applications. These new technologies generally named as warm mix asphalt (WMA) technologies implementing various techniques to reduce application temperatures in order to diminish harmful environmental effects of HMA applications and minimize construction costs. An effective technique to perform this task is to provide a foaming effect in mixing phase to increase workability by use of water containing additives such as zeolites. This paper investigates the feasibility of utilizing WMA containing natural zeolite additive in comparison with a commercial kind of synthetic zeolite. Marshall stability, indirect tensile stiffness moduli and fatigue behavior of WMA containing natural and synthetic zeolites have been analyzed and compared with HMA. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Warm mix asphalt; Natural zeolite; Synthetic zeolite; Marshall stability; Indirect tensile stiffness modulus; Fatigue behavior